VD_FINDINFO Jug / 2016 / 246 vom 7. September 2015 - VD Tribunal cantonal (2015)
CIRCULATION ROUTIÈREDROIT DE LA CIRCULATION ROUTIÈRE, PRINCIPE DE L'ACCUSATION, AMENDE | 106 CP, 26 al. 1 LCR, 27 al. 1 LCR, 90 al. 1 LCR, 14 al. 1 OCR, 325 al. 1 CPP (CH), 9 CPP (CH)